The Effect of Experimentally Induced Hypothyroidism on Neural Plasticity and Memory at First, Second and Third Trimester of Pregnancy - Donder, Emir; Ozkan, Yusuf; Dag, Said; Baydas, Giyaseddin (Ortadogu Ad Pres & Publ Co, 2010)
Objective: Thyroid hormone (TH) is very important for central nervous system (CNS) development. In critical periods of central nervous system development, TH deficiency delays retardation of glial cells and neurons maturation. Studies demonstrated that cell adhesion molecules (NCAM) have important roles on development of brain and synaptic plasticity. It was reported that TH deficiency causes abnormalities in synthesis and release of adhesion molecules. It was shown that glial fibrillar acidik protein (GFAP) was an important marker of astrocyte maturation. GFAP level decreases in astrocyte maturation defects. In this study, we investigated the effect of experimentally induced hypothyroidism at the first, second, and third trimester of pregnancy on neural plasticity and learning. Material and Methods: In our study; 15 infant Wistar Albino rats were taken from mothers in which experimentally induced hypothyroidism at the first, second, and third trimester of pregnancy. Fifteen infant rats were taken for the control group, totally 60 infant rats were used. Four groups were constituted in total. As learning test, widely used, the Morris Water Maze test was used. The levels of NCAM and GFAP were studied by the Western Sloth method. Results: Learning ability was increased gradually from the first to fifth day in four groups. This increase was more significant in control and first trimester hypothyroidism group when compared to second and third trimester hypothyroidism groups. We determined decrease in GFAP levels and all of NCAM isoforms of offspring hippocampus when they become adult in second and third trimester hypothyroid groups when compared to the control and first trimester hypothyroid groups. Conclusion: Our study demonstrated that experimentally induced hypothyroidism at the second and third trimester of pregnancy caused decrease in infant rats' learning ability and NCAM and GFAP levels at hypocampus.
Gebeli?in birinci, i?kinci ve üçüncü trimesterlerinde oluşturulan deneysel hipotiroidinin nöral plastisite ve ö?renmeye etkisi
Keywords: Neural cell adhesion molecules; glial fibrillary astrocytic protein, mouse; memory; learning; hypothyroidism